The potential of alley farming in humid West Africa - a re-evaluation - Sumberg, J.E.; Atta-Krah, A.N. (Springer, 1988)
Outlines a re-evaluation and a re-calculation of recently published hypothesis concerning the potential impact of alley farming on maize yields. Gives modifications and analysis based on the alley farming research of the International Livestock Center for Africa's (ILCA) Humid Zone Programme in Nigeria, and make some suggestions for future allely farming research.